Socio-Demographic Characteristics of COVID-19 Vaccine Recipients in Kwara State, North Central Nigeria - Al-Mustapha, Ahmad Ibrahim; Abubakar, Musa Imam; Oyewo, Muftau; Esighetti, Rita Enyam; Ogundijo, Oluwaseun Adeolu; Bolanle, Lukman Dele; Fakayode, Oluwatosin Enoch; Olugbon, Abdullateef Saliman; Oguntoye, Michael; Elelu, Nusirat (Frontiers in Public Health, 2022)
Understanding key socio-demographic variables of 2019 coronavirus disease (COVID-19) vaccine recipients is crucial to improving its acceptance and Nigeria's COVID-19 control strategy. The survey was conducted as a non-probability cross-sectional survey of 2,936 COVID-19 vaccine recipients in Kwara State. Our findings revealed that 74% (n = 2,161) of the vaccine recipients were older than 40 years. Forty percent (n = 1,180) of the vaccine recipients earned a monthly income >100,000 Naira (equivalent to US $200). Most of the vaccine recipients (64%, n = 1,880) had tertiary education, while 15% (n = 440) of them had no formal education. Almost half of the recipients (47%, n = 1,262) were government employees and 28.8% (n = 846) of them had health-related backgrounds. Only 17% (n = 499) of the vaccine recipients have been screened for the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), of which 21% (n = 105/499) of them were tested positive. Only 47% (n = 1,378) had been fully immunized. The prevalence of confirmed COVID-19 cases among COVID-19 vaccine recipients in Kwara State was 3.6% (n = 105/2,936). The most recurrent adverse events following immunization (AEFIs) among vaccine recipients were fever (14%, n = 411), pain at injection site (47%, n = 1,409), headache (19%, n = 558), and body weakness (9%, n = 264). The need to protect themselves from the deadly virus was the main reason that prompted people to voluntarily accept the COVID-19 vaccine. There is a high level of COVID-19 vaccine acceptance among respondents across all social classes including those with no formal education, those with very low monthly income (< US $2 per day), and in untested population. Hence, vaccine donors should prioritize equitable distribution to Low-and-Middle-income Countries (LMICs) such as Nigeria, and health authorities should improve vaccine advocacy to focus on vaccine safety and efficacy.